Pengaruh Metode Role-Playing Terhadap Peningkatan Kemampuan Berkomunikasi Anak Tunarungu Di SLB – B Karya Ibu - Tena, Irena Septian; Noviza, Neni; Putra, Bela Janare (Journal of Innovative and Creativity, 2026)
This study is titled "The Influence of the Role-Playing Method on Improving Communication Skills of Deaf Children at SLB-B Karya Ibu Palembang." The research is motivated by the critical role of communication as a fundamental skill for social interaction, whereas deaf children often face challenges in language acquisition due to hearing impairments. The objective of this study is to determine the impact of the role-playing method on enhancing the communication skills of deaf children at the specified school. This research employs a quantitative approach with an experimental method using a Pretest-Posttest Control Group Design. The research sample consists of 30 students, divided into 15 students for the experimental group and 15 students for the control group, selected through a purposive sampling technique. Data collection techniques included observation and communication skills tests, which were subsequently analyzed using the Mann-Whitney U non-parametric statistical test via SPSS version 26. The results indicate that the communication skills of the experimental group improved significantly, with the average score rising from 67.06 in the pretest to 87.53 in the posttest. In contrast, the control group only saw an increase from an average of 54.06 to 61.33. The Mann-Whitney U test yielded a significance value of 0.000 (< 0.05), leading to the conclusion that the role-playing method significantly influences the improvement of communication skills among deaf children at SLB-B Karya Ibu Palembang.